Kompetencje późnorzymskiego vicarius Thraciae w VI-VII wieku. - Wiewiorowski, Jacek (Wydawnictwo Poznańskie sp. z o.o., 2010)
The paper reviews the disputable issue concerning the competences of vicarius Thraciae (βικάριος Θρᾴκης), an office introduced during the rule of Justinian the Great (527-565) around the middle of the 6th century. Most probably a vicarius Thraciae was a civil head of four provinces of an ancient diocese of Thracia: Europa, Haemimontus, Rhodopa and Thracia. The author describes the administrative changes implemented in the Balkans in the Justinian the Great times, and presents various bits of information on other holders of that office, found on objects dug out in different parts of the territory, such as stamps or inscriptions. Those available data are subsequently compared with information on prerogatives of administrators of other dioceses. The author comes to the conclusion that judicial competences of a vicarius Thraciae were likely to be rather limited. His opinion is based on the fact that in appelate matters three out of the four provinces under the rule of the vicar were within the jurisdiction of the prefect of Constantinople. On the other hand, their purely administrative competences were much wider and included supervision of public construction projects. The author further proposes that a vicarius Thraciae might have had something to do with the defence construction project that was being realised in the Balkans in the Justinian the Great time. As one example shows, before 582 there was also a vicarius Thraciae who was most probably a military commander, others might have performed functions of heads of the army in emergency, when in the last decades of the 6th and 7th centuries Balkan provinces were threatened by the attacks of Avars and Slavs. In conclusion the author claims that the example of a vicarius Thraciae proves that the organisational principles on which a late-Roman state was built were not as formalised as some legal sources claim. This opinion is in line with the characteristic feature of the Roman state tradition which showed traces of certain instability of the principles on which a state was organised, and the ad hoc decisions that were often made by the state officials whenever a need for them arose.
COMPETENCES OF THE 6TH AND 7TH CENTURIES ROMAN VICARIUS THRACIAE.
Keywords: Cesarstwo Rzymskie; Reforma administracji; Justynian Wielki; Wikariusz